Flora of Espírito Santo: Bonnetiaceae - Marinho,Lucas Cardoso (2022)
Abstract Bonnetia stricta is the only species of Bonnetiaceae in eastern Brazil, where it occurs in the states of Alagoas, Bahia, Espírito Santo, Rio de Janeiro and Sergipe. It is easily recognized by the alternate, spiral leaves grouped at the apex of the branches and showy white to pink flowers with numerous stamens. As a contribution to the Flora of Espírito Santo project, this study provides a description, illustrations, taxonomic comments and a distribution map of the specimens of B. stricta from the state.